Pelaksanaan Pemutusan Hubungan Kerja (PHK) pada Yayasan Kesatuan Pendidikan Islam (YKPI) Al-Ittihad Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Efisa, Shindy; Bachtiar, Maryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The issue of the termination of employment relationships is an event which is not expected occurrence,therefore all parties involved in industrial relations (workers/employers, workers, unions/trade unions, andGovernment), with all the efforts should be organised so that it never happens to termination of employment. Inthe implementation of the termination of employment relationship employers must comply with and obey allregulations concerning employment that had been arranged by the Government, namely Act No. 13 of 2003 onLabor. The purpose of this study: first, know the termination work done Islamic Education Foundation of Unity(YKPI) Al-Ittihad complies or not with the regulations. Second, know the effort it can be done by workers whoare subject to termination of the working relationship. This type of research can be classified into types ofsociological research, because the author directly doing research on the location of the examined, in order togive a complete and clear picture of the problems examined. This research was conducted at the Foundation ofthe unity of Islamic education (YKPI) Al-Ittihad. Populations and samples in this study is a whole party thatdeals with issues that are examined. The source of the data in the study was obtained from primary data,secondary data, and tertiary data. Data collection techniques in the research interviews and study library.This type of research is classified into types of sociological research, because of the direct writers doingresearch on the locations studied, in order to provide a complete and clear picture of the issues examined. Thisresearch was conducted at the Foundation for Islamic Education Unit (YKPI) Al-Ittihad. Population andsample in this research is the overall party related to the problems examined. Sources of data in this study wereobtained from the primary data, secondary data, and the data tertiary. Data collection techniques in thisresearch is interview and literature study. Analysis of the data used is qualitative analysis and conclusions withdeductive thinking.From the results of the research can be concluded. First, the Foundation does not run theFoundation's regulations and does not perform the termination of the working relationship in accordance withthe rules of existing legislation, namely Act No. 13 of 2003 on Labor. Secondly, the case of the termination ofthe working relationship by the unity of Islamic education (YKPI) Al-Ittihad against Faizah Fahmi finishedthird and mediation the present Faizah Fahmi is entitled to severance money, 2 x money Awards workingperiod and the replacement of other rights money. First, the author's suggestion, it should be if the Foundationof the unity of Islamic education (YKPI) Al-Ittihad wanted to do termination of work (PHK) should be bound byemployment law and rules her Foundation. Second, the parties should have the Foundation employs backFaizah Fahmi because of the termination of such employment relationship simply because of the attitude ofFaizah Fahmi. There is no reason that a damning and harmful elements of the Foundation.Keywords: Foundation - Work relationship - Work Termination